INFORMATION TECHNOLOGY FOR MARKETING COMMUNICATION - W Novianti; E H Rahmah; T P Sumitra (LP2M Universitas Bina Bangsa, 2022)
The purpose of this research is to describe and analyze the benefits of Integrated marketing communication through Instagram social media in creating brand awareness, images, and good relationships with consumers in the applied business. In this case, the researchers focused on using the integration of Instagram marketing and effective social media communication. This research used qualitative approach with descriptive methods through interviews and literature studies. The results of this study indicate that the use of Integrated Marketing Communication (IMC) through social media has an influence in determining brand awareness, brand image, and deep relationships with customers. IMC through Instagram can help companies manage the message of a product to create brand awareness in customers